Information production and bidding in IPOs: An experimental analysis of auctions and fixed-price offerings - Andreas Trauten; Thomas Langer (Westfälische Wilhelms-Universität Münster, European Research Center for Information Systems (ERCIS), 2007)
Despite their theoretical efficiency in selling shares to the public, auctions are not the preferred mechanisms of issuers in Initial Public Offerings (IPOs). Chemmanur and Liu (2006) [WP] and Sherman (2005) [JFE 78, 615-649] provide a rational explanation for this IPO auction puzzle. They argue that issuers are not only interested in maximizing the offering proceeds, but also care about the secondary market price and thus try to induce many investors to produce information about the IPO. In fixed-price or bookbuilding offerings the issuer might opt to set an offering price that suggests underpricing in order to compensate investors for producing costly information. In auctions, however, competitive bidding impedes underpricing, which in turn lowers the incentive to produce information about the IPO in the first place. In this paper, we report an experimental study that was set up to test the mechanisms underlying this reasoning. Our findings strongly support the theoretical argument. In fixed-price offerings, the issuer can maintain investors' propensity to produce information by appropriately adjusting the offering price even if information costs are high. In auctions, however, high information costs inevitably result in a low propensity to produce information. This is a consequence of investors' competitive bidding behavior which prevents them from recovering the costs of information production. Our results provide experimental support for the theoretical argument that an auction is not the preferable offering mechanism for young and risky IPO firms since the costs of producing information about such firms are high, but there is also a strong need to generate information.
Keywords: 330